1986
DOI: 10.1152/jn.1986.56.4.987
|View full text |Cite
|
Sign up to set email alerts
|

PAD and PAH response patterns of group Ia- and Ib-fibers to cutaneous and descending inputs in the cat spinal cord

Abstract: The characteristics of the primary afferent depolarization (PAD) of Ia- and Ib-fibers generated by segmental and descending inputs have been analyzed in the spinal cord of anesthetized cats. The PAD was inferred from the changes produced by conditioning inputs on the intraspinal stimulus current required to produce a constant antidromic firing of single group I afferent fibers from the gastrocnemius (GS) or posterior biceps and semitendinosus (PBSt) nerves. Group I GS and PBSt fibers ending in the intermediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
56
0
1

Year Published

1987
1987
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(63 citation statements)
references
References 0 publications
6
56
0
1
Order By: Relevance
“…Note that, in the case of jaw muscles (Goldberg and Nakamura 1977), as well as in limb muscles (Rudomin and Schmidt, 1999), there is now evidence that cutaneous fibers can produce PAD in group I afferents. Reproduced from Eccles et al (1963) with permission of the American Physiological Society (see also Rudomin et al 1986). at any one time, had been previously observed by Barron and Matthews (1938b) and termed by them "dorsal root reflexes."…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that, in the case of jaw muscles (Goldberg and Nakamura 1977), as well as in limb muscles (Rudomin and Schmidt, 1999), there is now evidence that cutaneous fibers can produce PAD in group I afferents. Reproduced from Eccles et al (1963) with permission of the American Physiological Society (see also Rudomin et al 1986). at any one time, had been previously observed by Barron and Matthews (1938b) and termed by them "dorsal root reflexes."…”
Section: Reviewmentioning
confidence: 99%
“…Other studies, however, leave doubt as to whether the pyramidal tract is the main pathway involved. Thus when the motor cortex or the pyramidal tract are stimulated electrically, the PAD in group Ia afferents is inhibited rather than increased (Rudomin et al 1986;Eguibar et al 1994). Of the other descending pathways, those from the vestibular nuclei have been found to increase PAD in Ia fibers while stimulation of the red nucleus and reticular formation inhibited PAD; opposite effects were observed for Ib fibers (from tendon organs) while cutaneous fibers exhibited mixed effects (for review, see Rudomin and Schmidt 1999) However, these experiments, and indeed most of those employed in studies of PreI, made use of nonphysiological stimuli, massive simultaneous activation of fibers, and only analyzed events immediately after the shock.…”
Section: Descending Control Pathwaysmentioning
confidence: 99%
“…Since animal experiments have shown that cutaneous afferents project to spinal interneurones mediating presynaptic Ia inhibition (e.g. Rudomin, Sorodkin & Jimenez, 1986), we sought to test whether cutaneous input could affect presynaptic inhibition in the human forearm.…”
Section: Development Of Inward Rectification Inmentioning
confidence: 99%
“…It produces mono-and polysynaptic excitatory and inhibitory potentials in spinal motoneurones (Jankowska, Lund, Lundberg & Pompeiano, 1968;Peterson, 1984;Fung & Barnes, 1989;Takakusaki, Ohta & Mori, 1989), as well as dorsal root potentials (DRPs), the latter suggesting presynaptic inhibitory actions (Lundberg & Vyklicky, 1966;Proudfit & Anderson, 1974;Jimenez, Rudomin & Solodkin, 1987). At the time when this research was started, the available evidence indicated that electrical stimulation of the bulbar RF produced primary afferent depolarization (PAD) of tendon organ and of cutaneous afferents, and inhibited the PAD generated in muscle spindle afferents (Rudomin, Jimenez, Solodkin & Dueiias, 1983;Rudomin, Solodkin & Jimenez, 1986;Jimenez et al 1987;Jimenez, Rudomin & Solodkin, 1988;Rudomin, 1991 City, Mexico), diluted with isotonic saline (1:10) or dextran (10 %) was infused intravenously at a rate of 3 ml h-1 to maintain the blood pressure within this range. During paralysis, deep anaesthesia was maintained by i.v.…”
mentioning
confidence: 99%
“…At the end of the experiment, the stimulated brainstem sites were marked by passing anodic direct current (50 ,uA, 20-30 s) through the tungsten electrodes and the animal was killed with a overdose of anaesthetic and perfused with a 10% solution of prepared for histological verification of the stimulating sites and of the lesions (see Rudomin et al 1983 (Rudomin et al 1983). To this end, we used the 'threshold hunting method' described in detail elsewhere (Madrid, Alvarado, Dutton & Rudomin, 1979;Curtis, 1979;Rudomin et al 1983Rudomin et al , 1986) and summarized here. The glass micropipette was initially used to record the EFPs produced in the intermediate nucleus by stimulation with single pulses of the PBSt and GS nerves.…”
mentioning
confidence: 99%